A study of the driving factors of the intention and behavioral deviations of rural residents in waste classification - Zhang, Jie; Yu, Qidong; Chen, Qian (Frontiers in Environmental Science, 2024)
The deviation between the stated intentions and actual actions of rural residents about waste classification represents a significant obstacle to the effective implementation of environmental management strategies in rural areas. To enhance the governance of rural settlement environments and provide support for rural revitalization. This study establishes an analytical framework for examining the deviation between internal perceived efficacy and external environmental policies among rural residents. The relationship between intention and behavior can be classified into three distinct scenarios: The three scenarios are as follows: "intention with behavior," "intention without behavior," and "no intention with behavior." Furthermore, an empirical analysis is conducted using survey data collected by Nanjing Agricultural University in the China Land Economic Survey (CLES) in June and July 2021. The results show that: (1) the perceived efficacy has a significant positive influence on the deviation between rural residents' intention and behavior in domestic waste classification, while the environmental policy has a significant negative effect on it; (2) the guiding policy has a significant negative moderating effect on the influence of perceived efficacy on the deviation between rural residents' intention and behavior and the situation "with intention and without behavior", while the reward-punishment policy has a significant positive moderating effect on the influence of perceived efficacy on "without intention and behavior"; (3) the perceived efficacy has a masking effect on the impact of environmental policy on the deviation between rural residents' intention and behavior or "with intention and without behavior", and a partial mediating effect on the impact of environmental policy on "with intention and behavior" or "without intention and behavior". In light of these findings, the study puts forth policy recommendations that underscore the interconnectivity of government, village collective organizations, and rural residents. These recommendations encompass the implementation of environmental policies and initiatives aimed at enhancing rural residents' awareness of waste classification.